Evaluation of serum leptin levels in diabetic and hypertensive subjects resident in Port Harcourt - Waribo, Helen A.; Melex, Tamaradoubrah F.; Obisike, Uchechukwu A.; Ibioku, Elekima; Onwuli, Donatus O. (International Journal of Research in Medical Sciences, 2023)
Background: Diabetes and hypertension which are metabolic conditions are becoming more common and prevalent in the world. Prolonged rise of blood sugar levels, is a hallmark of diabetes, a metabolic condition caused by problems with insulin production, insulin resistance or both while hypertension is the persistent high blood pressure in the arteries. Leptin is a hormone that inhibits appetite, reduces fat storage in adipocytes and aids in the regulation of energy balance hence implicated in diabetes and insulin resistance. Thus, can metabolic state affects its level in the serum. Methods: The study population is two hundred and forty (240) subjects that are residents of Port Harcourt aged between 30-70 years. Sixty subjects were used as the control, sixty subjects were diabetes, the other sixty subjects were hypertensive while the remaining sixty were subjects with both hypertension and diabetic mellitus. An enzyme-linked immunosorbent assay (ELISA) method was used to quantitatively measure leptin levels in the serum sample, glycated haemoglobin were determined quantitatively using sandwich immunodetection and blood pressure was measured using mercury sphygmomanometer. Results: The data generated were statistically analysed using Graph Pad Prism version 9.0.2. The results showed no significant difference in leptin levels in diabetics, hypertensive and subjects having both diabetes and hypertension when compared with the control subjects having none of these metabolic disorders (p =0.4166). Conclusions: Our results shows that leptin levels in the population were relatively within the reference ranges both for males (0.5-12ng/ml) and females (0.5-15ng/ml). It clearly shows that metabolic conditions (diabetes or hypertension) does not affect leptin levels in serum.